The Trade Effects of Anti-Dumping Duties: Firm-Level Evidence from China - Gabriel Felbermayr; Alexander-Nikolai Sandkamp (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper uses Chinese customs data to investigate the trade effects of anti-dumping (AD) policies. Merging firm-level exports to firm-specific AD duties, we exploit differences across firms within products. This reduces endogeneity concerns which have plagued earlier research. Based on a firm-level gravity model, we find that, in line with literature, AD duties reduce exports, induce firm exit but do not affect producer prices. However, our strategy yields substantially larger estimates which differ strongly across sectors. More interestingly, imports to the EU react differently compared to those to the US; a finding with obvious implications for the design of AD policies. Smaller exporters are more heavily affected than larger ones, suggesting important within-industry reallocation effects. Moreover, we find evidence for trade deflection as AD duties lead to market entry of Chinese firms into third countries.
Keywords: F12; F13; F14; D22; 330; anti-dumping; China; trade; firm heterogeneity